Chromium-containing wastewater reclamation via forward osmosis with sewage sludge ash temperature-sensitive hydrogel as draw agent. (February 2023) - Pan, Zhihui; Yang, Xiongrui; Liang, Yilun; Lyu, Mengze; Huang, Yingru; Zhou, Hong; Wen, Gang; Yu, Huarong; He, Junguo
Abstract: A temperature-sensitive hydrogel modified with sewage sludge ash (SSA) was used as an advanced draw agent for forward osmosis (FO) application in treating chromium-containing wastewater. The performance of the modified hydrogel (SSA-TSH) was measured in terms of the swelling and deswelling properties, as well as adsorption and desorption effects on Cr(VI), chemical oxygen demand (COD), total phosphorous (TP) and ammonium (NH4 + -N) in chromium-containing wastewater. Furthermore, the efficiencies of wastewater treatment, water flux, and the reusability of the SSA-TSH as draw agent in the FO process (FO-SSA-TSH) using a commercially available thin-film composite membrane (Sterlitech) were also investigated. The results indicated that FO-SSA-TSH achieved high removal rates of pollutants (Cr(VI): 96.9 %–97.4 %, COD: 97.1 %–97.4 %, TP: 97.7 %–99.6 %, and NH4 + -N: 76.8 %–77.9 %) in various Cr(VI) concentrations (0– 40 mg/L) due to the high rejection rate of FO membrane and notable adsorption capacity of the hydrogel. Moreover, the average water flux of FO-SSA-TSH (1.95– 2.02 LMH) was nearly twice as much as that of the FO with pure temperature-sensitive hydrogel as draw agent (FO-TSH, 1.33– 1.42 LMH) in 24 h chromium-containing wastewater treatment. In addition, SSA-TSH with excellent deswelling property exhibited high water recovery performance and good reusability in low cost and energy consumption after the FO permeation process for wastewater treatment. Graphical abstract: Unlabelled Image Highlights: FO with SSA-based hydrogel as draw agent for Cr-containing wastewater reclamation. SSA enhanced swelling ability and pollutants adsorption capacity of hydrogel. High pollutant removal rates and water flux were achieved in FO-SSA-TSH. Low energy consumption for water recovery and hydrogel regeneration.